2021
DOI: 10.1371/journal.pone.0245288
|View full text |Cite
|
Sign up to set email alerts
|

Economic and epidemiological evaluation of interventions to reduce the burden of hepatitis C in Yunnan province, China

Abstract: Background The paradigm shift in hepatitis C virus (HCV) treatment options in the last five years has raised the prospect of eliminating the disease as a global health threat. This will require a step-change in the number being treated with the new direct-acting antivirals (DAAs). Given constrained budgets and competing priorities, policy makers need information on how to scale-up access to HCV treatment. To inform such decisions, we examined the cost effectiveness of screening and treatment interventions in Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…China has one of the largest burden of HCV with an estimated 7.6 million HCV infections at the start of 2016 (3). Investment cases for HCV elimination demonstrated good returns on investment and cost savings (26,27). The 2017-2020 national plan for prevention and control of viral hepatitis articulated a framework for action by multiple stakeholders.…”
Section: Chinamentioning
confidence: 99%
“…China has one of the largest burden of HCV with an estimated 7.6 million HCV infections at the start of 2016 (3). Investment cases for HCV elimination demonstrated good returns on investment and cost savings (26,27). The 2017-2020 national plan for prevention and control of viral hepatitis articulated a framework for action by multiple stakeholders.…”
Section: Chinamentioning
confidence: 99%
“…[ 24 ] Heffernan and associates in China found that switching to DAAs is cost effective 94% of the time. [ 25 ] In India, Chaillon et al . found that treating all diagnosed individuals with moderate-sever liver disease remained cost-saving compared to no treatment with all reinfection rates evaluated.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Cost data Anti-HCV test per unit 3.14 (2.35–3.92) Gamma (784.88, 0.004) Heffernan et al. 27 HCV-RNA test per unit 43.95 (32.97–54.94) Gamma (15.1, 2.91) Heffernan et al. 27 Pan genotypic DAA per patient 1,781 (1,530–2,032) Gamma (24735, 0.072) Chinese list prices Annually managing F0–F3 HCV disease 924 (625–1,223) Gamma (5601, 0.165) Zhou et al.…”
Section: Methodsmentioning
confidence: 99%